Fighting consumer price inflation in Africa. What do dynamics in money, credit, efficiency and size tell us? - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
Purpose The purpose of this paper is to examine the effects of policy options in financial dynamics (of money, credit, efficiency and size) on consumer prices. Soaring food prices have marked the geopolitical landscape of African countries in the past decade. Design/methodology/approach We limit our sample to a panel of African countries for which inflation is non-stationary. VAR models from both error correction and Granger causality perspectives are applied. Analyses of dynamic shocks and responses are also covered. Six batteries of robustness checks are applied to ensure consistency in the results. Findings (1) There are significant long-run equilibriums between inflation and each financial dynamic. (2) When there is a disequilibrium, while only financial depth and financial size could be significantly used to exert deflationary pressures, inflation is significant in adjusting all financial dynamics. In other words, financial depth and financial size are more significant instruments in fighting inflation than financial efficiency and activity. (3) The financial intermediary dynamic of size appears to be more instrumental in exerting a deflationary tendency than financial intermediary depth. (4) The deflationary tendency from money supply is double that based on liquid liabilities. Practical implications Monetary policy aimed at fighting inflation only based on bank deposits may not be very effective until other informal and semi-formal financial sectors are taken into account. It could be inferred that, tight monetary policy targeting the ability of banks to grant credit (in relation to central bank credits) is more effective in tackling consumer price inflation than that, targeting the ability of banks to receive deposits. In the same vein, adjusting the lending rate could be more effective than adjusting the deposit rate. The insignificance of financial allocation efficiency and financial activity as policy tools in the battle against inflation could be explained by the (well documented) surplus liquidity issues experienced by the African banking sector. Social implications This paper helps in providing monetary policy options in the fight against soaring consumer prices. By keeping inflationary pressures on food prices in check, sustained campaigns involving strikes, demonstrations, marches, rallies and political crises that seriously disrupt economic performance could be mitigated. Originality/value As far as we have perused, there is yet no study that assesses monetary policy options that could be relevant in addressing the dramatic surge in the price of consumer commodities.
Keywords: E31; G20; O10; O55; P50; 330; Banks; Inflation; Development; Panel; Africa